Diverse landscapes beneath Pine Island Glacier influence ice flow - Bingham, RG; Vaughan, DG; King, EC; Davies, D; Cornford, SL; Smith, AM; Arthern, RJ; Brisbourne, AM; De Rydt, J; Graham, AGC; Spagnolo, M; Marsh, OJ; et al. (Nature Communications, 2017)
This is the final version of the article. Available from Springer Nature via the DOI in this record. The retreating Pine Island Glacier (PIG), West Antarctica, presently contributes ~5–10% of global sea-level rise. PIG’s retreat rate has increased in recent decades with associated thinning migrating upstream into tributaries feeding the main glacier trunk. To project future change requires modelling that includes robust parameterisation of basal traction, the resistance to ice flow at the bed. However, most ice-sheet models estimate basal traction from satellite-derived surface velocity, without a priori knowledge of the key processes from which it is derived, namely friction at the ice-bed interface and form drag, and the resistance to ice flow that arises as ice deforms to negotiate bed topography. Here, we present high-resolution maps, acquired using ice-penetrating radar, of the bed topography across parts of PIG. Contrary to lower-resolution data currently used for ice-sheet models, these data show a contrasting topography across the ice-bed interface. We show that these diverse subglacial landscapes have an impact on ice flow, and present a challenge for modelling ice-sheet evolution and projecting global sea-level rise from ice-sheet loss. This work was supported by funding from the UK Natural Environment Research Council (NERC) iSTAR Programme (Grants NE/J005665 and NE/K011189), NERC grants NE/B502287/1 and NE/J004766/1 and the British Antarctic Survey (BAS) Polar Science for Planet Earth Programme. D.E.S. was supported by a NASA NESSF fellowship (NNX12AN36H). Bathymetric data used for Fig. 2c and f were sourced from the Bolin Centre Database Oden Mapping Data (cruise OSO 0910; http://oden.geo.su.se/oso0910) and NSF/IEDA Marine Geoscience Data System (http://www.marine-geo.org/tools/search/Files.php?data_set_uid=20080) respectively, and we thank the lead authors M. Jakobsson and F.O. Nitsche for their lodging. All fieldwork was supported by the staff at BAS’s Rothera Research Station and members of ...